The microRNA network is altered in anterior cingulate cortex of patients with unipolar and bipolar depression. (November 2016) - Azevedo, Joshua A.; Carter, Bradley S.; Meng, Fan; Turner, David L.; Dai, Manhong; Schatzberg, Alan F.; Barchas, Jack D.; Jones, Edward G.; Bunney, William E.; Myers, Richard M.; Akil, Huda; Watson, Stanley J.; et al.
Abstract: MicroRNAs (miRNAs) are small, non-coding RNAs acting as post-transcriptional regulators of gene expression. Though implicated in multiple CNS disorders, miRNAs have not been examined in any psychiatric disease state in anterior cingulate cortex (AnCg), a brain region centrally involved in regulating mood. We performed qPCR analyses of 29 miRNAs previously implicated in psychiatric illness (major depressive disorder (MDD), bipolar disorder (BP) and/or schizophrenia (SZ)) in AnCg of patients with MDD and BP versus controls. miR-132, miR-133a and miR-212 were initially identified as differentially expressed in BP, miR-184 in MDD and miR-34a in both MDD and BP (although none survived multiple correction testing and must be considered preliminary). In silico target prediction algorithms identified putative targets of differentially expressed miRNAs. Nuclear Co-Activator 1 ( NCOA1 ), Nuclear Co-Repressor 2 ( NCOR2 ) and Phosphodiesterase 4B ( PDE4B ) were selected based upon predicted targeting by miR-34a (with NCOR2 and PDE4B both targeted by miR-184 ) and published relevance to psychiatric illness. Luciferase assays identified PDE4B as a target of miR-34a and miR-184, while NCOA1 and NCOR2 were targeted by miR-34a and 184, respectively. qPCR analyses were performed to determine whether changes in miRNA levels correlated with mRNA levels of validated targets. NCOA1 showed an inverse correlation with miR-34a in BP, while NCOR2 demonstrated a positive correlation. In sum, this is the first study to demonstrate miRNA changes in AnCg in psychiatric illness and validate miR-34a as differentially expressed in CNS in MDD. These findings support a mechanistic role for miRNAs in the regulation of stress-responsive genes disrupted in psychiatric illness.